An ethnobotanical survey of medicinal and edible plants of Yalo Woreda in Afar regional state, Ethiopia - Tilahun Teklehaymanot (BMC, 2017)
Abstract Background The Afar people inhabit the sub-arid and arid part of Ethiopia. Recurrent drought and invasive encroaching plants are taking out plants that have cultural importance, and threaten the biodiversity and the associated traditional knowledge. Thus, the aim of the current study is to conduct an ethnobotanical survey and document medicinal and edible plants in Yalo Woreda in Afar regional state. Methods A cross-sectional ethnobotanical study was carried out in eight kebeles of Yalo Woreda from October 2015 to December 2016. One hundred sixty informants were selected using purposive sampling. The data on diseases, medicinal and edible plants were collected using semi-structure interview and group discussion. The statistical methods, informant consensus factor, fidelity level, and preference ranking were conducted to analyze the data. Results One hundred and six plants were reported; gender and age differences had implication on the number of plants reported by informants. The knowledge of medicinal plants among informants of each kebele was not different (p < 0.5) and was not associated in particular with the religious establishment in the kebeles (informant*kebeles, Eta square = 0.19). Family Fabaceae was the major plant species, and shrubs (44%) were dominant plants reported. Leaf (52.94%) and oral (68%) were primary plant part used for remedy preparation and route of application, respectively. The plants with low fidelity values Indigofera articulata (0.25), Cadaba farinosa (0.22), Cadaba rotundifolia (0.19), and Acalypha fruticosa (0.15) were used to treat the category of diseases with high informant consensus value (0.69). Sixteen edible plants were identified that were consumed during wet and dry seasons. Balanites aegyptiaca, Balanites rotundifolia, and Dobera glabra were 'famine food' that were collected and stored for years. Conclusion People in Yalo Woreda are more dependent on natural resources of the area for their livelihood. The threat of climatic change and encroaching invasive plants on medicinal and edible plants affects the traditional use of plants in the Yalo Woreda. The conservation of the plants in the home garden and natural habitat and integration of edible plants into agroforestry development programs in sub-arid and arid regions has to be encouraged to conserve plants of medical and economic importance.